45.)
$\displaystyle \lim_{x \to -1} \frac {2x^2-x- 3}{x^3+2x^2+6x+5} = ?$
Because both the numerator and denominator are well behaved at $\displaystyle x=1$ the limit may be evaluated by substituting $\displaystyle 1$ for $\displaystyle x$ so:
$\displaystyle
\lim_{x \to 1} \frac {2x^2-x- 3}{x^3+2x^2+6x+5} = \frac{-2}{14}=-\frac{1}{7}
$
RonL
Hello Ranger SVO.
May I ask, if it's not too much trouble, how you managed to post the screen from your Voyage 200?. I have a TI-92 with the GraphLink; I have my programs backed up and so forth, but I've not done that. I know if I try, I'll probably get some annoying error message.